2005
DOI: 10.1002/art.20711
|View full text |Cite
|
Sign up to set email alerts
|

C‐reactive protein as a predictor of infliximab treatment outcome in patients with rheumatoid arthritis: Defining subtypes of nonresponse and subsequent response to etanercept

Abstract: Infliximab NRs comprise subtypes with distinct CRP patterns. Failure to suppress the CRP at week 2 identified the majority of patients who were NRs at week 12. CRP suppression at week 12 in the NRs was associated with a late clinical improvement with infliximab treatment (24 weeks), whereas failure to suppress the CRP at week 12 was associated with a good response on switching to etanercept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
1
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 12 publications
1
62
1
3
Order By: Relevance
“…However, we were unable to draw a definitive conclusion in this study, and additional studies with a larger number of samples should be performed to confirm our observations and speculations. In a recent study, it was shown that failure to suppress serum CRP at week 2 of therapy identified the majority of patients who were nonresponders by week 12 (47). However, in our series of patients, we did not find a significant relationship between a reduction in the CRP level at week 2 and the efficacy of infliximab at week 54.…”
Section: Discussioncontrasting
confidence: 88%
“…However, we were unable to draw a definitive conclusion in this study, and additional studies with a larger number of samples should be performed to confirm our observations and speculations. In a recent study, it was shown that failure to suppress serum CRP at week 2 of therapy identified the majority of patients who were nonresponders by week 12 (47). However, in our series of patients, we did not find a significant relationship between a reduction in the CRP level at week 2 and the efficacy of infliximab at week 54.…”
Section: Discussioncontrasting
confidence: 88%
“…In the studies by Buch et al 99 and Bingham et al 104 lack of efficacy was the primary reason for switching to ETN. In studies by Haraoui et al, 98 Cohen et al 100 and Buch et al 101 patients discontinued IFX owing to a lack of efficacy or safety.…”
Section: Etanerceptmentioning
confidence: 99%
“…Seven uncontrolled observational studies [98][99][100][101][102][103][104] were identified that assessed efficacy of ETN.…”
Section: Etanerceptmentioning
confidence: 99%
See 2 more Smart Citations